Continuity and change in cultural adaptation to mountain environments : from prehistory to contemporary threats - Lozny, Ludomir R. (Studies in Human Ecology and Adaptation, 2013)
Continuity and Change in Cultural Mountain Adaptations: From Prehistory to Contemporary Threats presents an international and interdisciplinary account of human cultural adaptation to mountainous environments over time. Mountain ecosystems are critical to the wellbeing of sizable populations in Eurasia, the Americas, and Africa. The book presents the evidence on continuity of human cultural adaptation to mountain ecosystems and also on contemporary threats and vulnerabilities caused by intensification in mining, agriculture, and tourism.  The essays collected here discuss human responses to key physical and cultural stressors impacting human wellbeing in mountain ecosystems, such as aridity, quality of soils, steep slopes, industrialization and infrastructural change, low productivity, adverse effects of centralized political decision-making, deforestation and erosion, tourism, and the possible effects of climate change. The contributors who are cultural anthropologists, geographers, archaeologists, ecologists, and cultural resource managers and planners all point out that mountain populations cope with the stressors by adopting specific cultural strategies, such as seasonal migrations, integration of pastoral and agricultural production, animal crossbreeding, use of crop varieties, a mixture of communal and household control of land, trade, crop diversity, diversification of activities, and technological innovations and innovative scheduling of productive activities.  Continuity and Change in Cultural Mountain Adaptations: From Prehistory to Contemporary Threats will be of interest to archaeologists, cultural resource managers, anthropologists, ecologists, climatologists, and geologists because mountainous ecosystems change fast, and cultures disappear and they need to be recorded.  Most importantly, cultural responses of mountain populations provide clues for us all in this time of environmental change.